1998
DOI: 10.1016/s0092-8674(00)81437-3
|View full text |Cite
|
Sign up to set email alerts
|

FGF and Shh Signals Control Dopaminergic and Serotonergic Cell Fate in the Anterior Neural Plate

Abstract: During development, distinct classes of neurons are specified in precise locations along the dorso-ventral and anterior-posterior axes of the neural tube. We provide evidence that intersections of Shh, which is expressed along the ventral neural tube, and FGF8, which is locally produced at the mid/hindbrain boundary and in the rostral forebrain, create induction sites for dopaminergic neurons in the midbrain and forebrain. The same intersection, when preceded by a third signal, FGF4, which is expressed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
599
2
7

Year Published

1999
1999
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 795 publications
(629 citation statements)
references
References 55 publications
21
599
2
7
Order By: Relevance
“…A second pathway involving Lmx1b and Ptx3 seems to be important for expression of other aspects of the dopaminergic neuronal phenotype [36]. Shh and FGF8 induce the dopaminergic phenotype when present in appropriate concentrations in specific brain regions [33,37,38]. The receptor for Shh is Smo, which is inhibited by a second protein patched (ptch) when Shh is absent [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…A second pathway involving Lmx1b and Ptx3 seems to be important for expression of other aspects of the dopaminergic neuronal phenotype [36]. Shh and FGF8 induce the dopaminergic phenotype when present in appropriate concentrations in specific brain regions [33,37,38]. The receptor for Shh is Smo, which is inhibited by a second protein patched (ptch) when Shh is absent [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 5% of the transcripts in the hypothalamic DA neurons differed from those of the SN or VTA neurons. DA neurons in the midbrain and hypothalamus each expressed specific sets of transcriptional regulators, suggesting that although both neuronal classes depend on Fgf8 and Shh for their early specification (42), their later phenotype is maintained, in part, by independent regulatory cascades. Such a cascade would include the DA midbrain-and forebrain-specific transcription factors PBX1, ZFH-4, IFI 116, Bteb2, Lmo2, Prox1, and Hnf-6 that have been identified here, as well as the known transcriptional regulators of DA differentiation and survival Nurr1, Lmx1b, and Pitx3.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work identified SHH and FGF8 as crucial factors in the specification of midbrain DA neurons (24). These studies in explant culture and subsequent work with mouse ES cells (2,11,22) demonstrated that the effect of SHH and FGF8 on dopaminergic differentiation is limited to distinct developmental windows that correspond to the establishment of the isthmic organizer and events controlling dorsoventral patterning during neural tube closure.…”
Section: Patterning and Differentiation Of Neural Precursors From Es-mentioning
confidence: 97%